Rhinos - Holmes, Kevin J. (Mankato, Minn. : Bridgestone Books, 2000)
This book describes the physical characteristics, behavior, habitat, and endangered status of the rhino.
Includes index.
Includes glossary.
Includes bibliography.
K-3
AR Accelerated Reader
Keywords: Rhinoceroses; Endangered species